2010
DOI: 10.1007/s13131-010-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of sea fog with different airflow over the Huanghai Sea in boreal spring

Abstract: Using the observations from ICOADS datasets and contemporaneous NCEP/NCAR reanalysis datasets during 1960-2002, the study classifies the airflows in favor of sea fog over the Huanghai (Yellow) Sea in boreal spring (April-May) with the method of trajectory analysis, and analyzes the changes of proportions of warm and cold sea fogs along different paths of airflow. According to the heat balance equation, we investigate the relationships between the marine meteorological conditions and the proportion of warm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The presence of temperature and salinity inversions in the YS has long been recognized (Kim et al, 2020;Lie et al, 2015Lie et al, , 2019Zhou et al, 2004;Zou et al, 2000Zou et al, , 2001. However, previous studies mainly focused on temperature inversions in cold seasons with the presence of salinity inversions largely ignored (Yang et al, 2023;Zhou et al, 2004). Here we show that temperature inversions not only exist in spring but also in summer.…”
Section: Generation and Water-mass Transformation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of temperature and salinity inversions in the YS has long been recognized (Kim et al, 2020;Lie et al, 2015Lie et al, , 2019Zhou et al, 2004;Zou et al, 2000Zou et al, , 2001. However, previous studies mainly focused on temperature inversions in cold seasons with the presence of salinity inversions largely ignored (Yang et al, 2023;Zhou et al, 2004). Here we show that temperature inversions not only exist in spring but also in summer.…”
Section: Generation and Water-mass Transformation Mechanismmentioning
confidence: 99%
“…Furthermore, apart from the temperature inversions as mentioned above, it should be noted that there also exist salinity inversions in the YS which is far from well-studied. Zhou et al (2004) first observed the presence of middepth Low Salinity Water (LSW) near the Subei coast and Cheng Shantou-Shi Dao to area near the Qingdao Cold Water Mass (QDCWM) from spring to early summer. They further suggested that the LSW may be originated from the western coastal regions and intruded into the center of YS, albeit this driving mechanism remain to be validated.…”
Section: Introductionmentioning
confidence: 99%
“…As an air mass travels over the Yellow Sea along the path of C3, there is the sharpest decrease in the underlying sea surface temperatures. The origin of air masses is closely associated with atmospheric circulations (Huang et al, 2010(Huang et al, , 2018Kim and Yum, 2010;Zhang et al, 2011;Yang et al, 2018). Therefore, to investigate various atmospheric spatial patterns and their related physical processes over the Yellow Sea, we measured the composite anomalies of geopotential height and horizontal wind vectors at 1,000 hPa, vertical cross-section of air temperature and specific humidity from 1,000 to 700 hPa, and temperature differences for the four primary airflow paths (Figure 6).…”
Section: Major Airflow Paths Associated With Fog Eventsmentioning
confidence: 99%
“…The key factor in a sea fog episode is the saturation level of the near-surface air. The trajectory analysis of an air mass, introduced by Taylor [6], is a widely utilized and effective method to diagnose the cooling and moistening during advection [7,11,12,[49][50][51]. According to Heo and Ha [52], most advection fog occurs when the air temperature is approximately 1-2 • C warmer than the SST.…”
Section: Backward Trajectory Analysismentioning
confidence: 99%